Penerapan Water Tepid Sponge Terhadap Penurunan Suhu Tubuh Anak dengan Hipertermia di Ruang Anak RST Bhakti Wira Tamtama Semarang - Fitri Dwi Aprilia; Witri Hastuti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study employs a descriptive method with a case study approach. The participants in this research were pediatric patients who suffered from hyperthermia. The non-pharmacological intervention of tepid water sponge compresses is utilized effectively to lower body temperature in children. The compresses are applied to the forehead and axillary regions, and this procedure is conducted for 3 days, with each compress lasting 15 minutes. The findings from this study over the course of 3 days indicate that the use of tepid water sponge compresses is effective in reducing body temperature in children with hyperthermia.